CHINESE AMERICANS’ ACCULTURATION IN GISH JEN’S TYPICAL AMERICAN - Melania Shinta Harendika (Jurnal Bahasa, Sastra, dan Studi Amerika, 2020)
Gish Jen’s Typical American is a portrayal of Chinese immigrants’ struggles in adapting the life in America (USA). The main characters started to live in the USA; they, however, were struggling in trying to maintain their Chinese values as well as embracing the new American culture. In the process of adjusting this new culture, they had to cope with things that were not always suitable for their prior culture as Chinese. It is found that there are two dominant types of acculturation process presented by the characters in this novel: (1) separation when Ralph’s family maintained their original culture through family reunification and Chinese women’s role perpetuation in the family; and (2) assimilation shown by the rejections to maintain their original culture since the main characters have been influenced by American doctrines. It reveals also that in Gish Jen’s Typical American, acculturation was one of the ways to cope with the culture shock that they experienced as the first generation of Chinese immigrants in the USA. This research reveals also that cultural values were something fluid, although there were differences between Chinese and American cultures that affect one's belief, they were able to adapt to the new culture with some adjustments.